2013
DOI: 10.1021/jp405342v
|View full text |Cite
|
Sign up to set email alerts
|

Between Peptides and Bile Acids: Self-Assembly of Phenylalanine Substituted Cholic Acids

Abstract: Biocompatible molecules that undergo self-assembly are of high importance in biological and medical applications of nanoscience. Peptides and bile acids are among the most investigated due to their ability to self-organize into many different, often stimuli-sensitive, supramolecular structures. With the aim of preparing molecules mixing the aggregation properties of bile acid and amino acid-based molecules, we report on the synthesis and self-association behavior of two diastereomers obtained by substituting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 68 publications
(118 reference statements)
1
37
0
Order By: Relevance
“…Molecules that arrange into tubules are often observed. In some cases, tubules can present stimuli-responsive features as well as tunable size or charge [35][36][37][38][39][40][41][42]. A plentitude of low molecular weight gelators formed by BA derivatives have been also investigated [30,[43][44][45][46].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Molecules that arrange into tubules are often observed. In some cases, tubules can present stimuli-responsive features as well as tunable size or charge [35][36][37][38][39][40][41][42]. A plentitude of low molecular weight gelators formed by BA derivatives have been also investigated [30,[43][44][45][46].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Upon this assumption, the best fit (Fig.S2) was The n agg and N Hyd values for the micelles were then estimated from the IFT extrapolated SAXS intensity I(0) = 0.032 ± 0.001 cm -1 , as described in detail in a previous work [45]. Since the β-LTrpC micelles were similar to those formed by HC (the natural precursor) in analogous conditions, in terms of both size and shape [28], an ionization degree α of 0.8 was used in the calculations, according to the α values (0.79-0.85) usually reported for the micelles formed by the precursor [57][58][59]. A n agg value of 6.4 ± 0.1 was estimated, in agreement with the range of n agg values (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) reported in the literature for the HC micelles [57,60].…”
Section: Self-assembly Of -L-trpc In Alkaline Solutionsmentioning
confidence: 99%
“…For example, the functionalization of both the side chain and the tetracyclic system is observed to lead to efficient gelators in organic solvents as well as in aqueous solutions [22], and the possibility to enhance their efficiency by using catanionic mixtures of the derivatives was demonstrated [23], whereas the BAs functionalized in their rigid backbone, selfassemble into lamellae or tubules [24][25][26][27][28][29][30]. In particular, the selective substitution of one of the steroid hydroxyl groups by an adamantly group gives derivatives that self-organize in lamellar arrays [24], whereas the introduction of an aromatic residue gives compounds able to self-associate into tubular structures [26][27][28][29][30][31][32][33][34] showing sometimes unique features such as extremely narrow cross sections [27,28], thermo- [33,34] or pH-responsive aggregations [32] and catanionic controlled Page 3 of 25 A c c e p t e d M a n u s c r i p t 4 compositions [31]. Tubular structures are also formed by BA molecules substituted with monosaccharide residues through an unusual mechanism involving scrolls as intermediates [25], whereas vesicles are given by some Gemini derivatives [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[13][14][15] Furthermore, self-assembly of amino acid derivatized BS has been widely investigated as a potential strategy for the preparation of nanostructured biomaterials with a wide range of applications in nanomedicine. [16][17][18] We have recently demonstrated that derivatization of CA by incorporating a dansyl (Dns) fluorophore, 19,20 which exhibits a strongly medium-dependent photophysical behavior, affords Fluorescence quenching of self-assemblies based on 3β β β β-DnsCA or 3β β β β-NPX-CA A further piece of evidence supporting formation of new 3β-Dns-CA or 3β-NPX-CA assemblies at 40-70 µM concentration was obtained from quenching experiments using iodide ( Figures 4 and S5). 22,26 Rate constant values (kq) were determined for 3β-Dns-CA and 3β-NPX-CA at two different concentrations: 16 µM (still in solution) and 100 µM (forming self-assemblies).…”
Section: Introductionmentioning
confidence: 99%